Legal Analysis of Strategies for Regional Institutional Reform to Advance Democratic Governance - Risman Setiawan (Journal of State Democracy, 2026)
The institutional framework of local government in Indonesia faces challenges from covert centralism, which restricts democratic processes at the local level. This study applies a normative legal method, using statutory and conceptual approaches, to examine the direction of legal policies that shape local government institutions. Unlike previous studies that discuss public management, this research emphasizes the integration of constitutional democratic values into the design of local governance structures. Its objective is to propose a reconstruction of institutional policy that strengthens democratic governance. The findings show that strict central government standardization creates a democratic deficit and reduces the oversight capacity of the Regional People’s Representative Council (DPRD) over the executive branch. The criminalization of local policy discretion also hinders governance innovation. The study concludes that local governance requires a model balancing administrative efficiency and popular sovereignty. Public policy must harmonize regulations, ensure legal certainty, and support responsive, innovative, democratic regional institutions.